Interactions of Paracoccidioides brasiliensis with host cells: recent advances - Mendes-Giannini, Maria José Soares [UNESP]; Monteiro da Silva, Juliana Leal [UNESP]; da Silva, Julhiany de Fatima [UNESP]; Donofrio, Fabiana Cristina [UNESP]; Miranda, Elaine Toscano [UNESP]; Andreotti, Patricia Ferrari [UNESP]; Soares, Christiane Pienna [UNESP] (Springer, 2008)
Host-fungal interactions are inherently complex and dynamic. In order to identify new microbial targets and develop more effective anti-fungal therapies, it is important to understand the cellular and molecular mechanisms of disease. Paracoccidioidomycosis provokes a variety of clinical symptoms, and Paracoccidioides brasiliensis can reach many tissues, but primarily attacks the lungs. The ability of the pathogen to interact with the host surface structures is essential to further colonization, invasion, and growth. Epithelial cells may represent the first host barrier or the preferential site of entry of the fungus. For this reason, interactions between P. brasiliensis and Vero/A549 epithelial cells were evaluated, with an emphasis on the adherence, induction of cytoskeletal alterations, and differential signaling activity of the various surface molecules. The adhesion to and invasion of epithelial cells by P. brasiliensis may represent strategies employed to thwart the initial host immune response, and may help in the subsequent dissemination of the pathogen throughout the body.
Keywords: Paracoccidioides brasiliensis; host-fungal interaction; adhesion; cytoskeleton; apoptosis; virulence factors